Nurturing resilience in smallholder farming systems: Emerging insights from a Climate-Smart Village in Southern Shan State, Myanmar - Barbon, Wilson John; Myae, Chan; Su, Myat Noe; Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The brief talks about the emerging insights from a Climate-Smart Village in Southern Shan State, Myanmar. It documents a range of coping strategies that help farmers deal with impacts of climate change.